Behavioral Responses to Wealth Taxation: Evidence from a Norwegian Reform - Roberto Iacono; Bård Smedsvik (CESifo GmbH, 2024)
How do wealthy individuals respond to wealth tax reforms? We analyse behavioral responses to intensive margin variation in wealth tax rates, estimating the causal effects of an unprecedented municipal wealth tax reform in Norway. We leverage variation from the single-period municipal reform reducing the marginal tax rate (MTR) on wealth exclusively in the northern Norwegian municipality of Bo from 0.85% to 0.35%, since 2021. Mimicking the behaviour of a tax haven, Bo represents the first municipality in Norway to unilaterally reduce the municipal wealth tax rate since 1978. We document a significant 60% increase in average taxable wealth in response to a 1 percentage point drop in the wealth tax rate. The elasticity of taxable wealth increases to 68.7% when focusing exclusively on wealth taxpayers. We also estimate a significant but more modest 10% jump in the weighted mass of wealth taxpayers in the treated municipality. Migration effects of the reform dominate: internal mobility of wealthy taxpayers appears as the major behavioral response to the change in the net tax rate, accounting for a large portion of the post-treatment total net wealth in the treated municipality. While these effects are pronounced at the municipal level, they do not suggest a large-scale exodus at the national level, indicating that migration to avoid wealth taxation is not necessarily an inevitable outcome of localized preferential tax regimes. These results emerge in a context of third-party reported wealth data with minimal measurement error, limited evidence of bunching, highly enforced residence-based wealth taxation, and negligible out-migration rates.
Keywords: H20; H21; H24; H26; 330; wealth taxation; behavioral responses; tax avoidance; migration